Angels & Demons - Brown, Dan, 1964- (New York : Pocket Star Books, 2001)
An ancient secret brotherhood. A devastating new weapon of destruction. An unthinkable target. World-renowned Harvard symbologist Robert Langdon is summoned to a Swiss research facility to analyze a cryptic symbol seared into the chest of a murdered physicist. What he discovers is unimaginable : a deadly vendetta against the Catholic Church by a centuries-old underground organization -- the Illuminati. Desperate to save the Vatican from a powerful time bomb, Langdon joins forces in Rome with the beautiful and mysterious scientist Vittoria Vetra. Together they embark on a frantic hunt through sealed crypts, dangerous catacombs, deserted cathedrals, and the most secretive vault on earth...the long-forgotten Illuminati lair.
"1st Pocket Books paperback edition July 2001."
Keywords: Physicists -- Crimes against; Fiction; Religious educators -- Fiction; Popes -- Election; Fiction; Signs and symbols -- Fiction; Secret societies -- Fiction; Anti-Catholicism -- Fiction; Illuminati -- Fiction; Vendetta -- Fiction; Papacy -- Fiction; Vatican City -- Fiction; Suspense fiction; Adventure fiction